Semantic and syntactic: Filipino high school students' reversal errors in translating mathematical word problems into algebraic equations - Mangulabnan, Pauline Anne Therese M. (Animo Repository, 2024)
This is a descriptive phenomenological study on the reversal errors committed by 108 high school senior students. Such reversal errors - semantic and syntactic - had been defined and discussed by John Clement in his studies on the translation of mathematical word problems into algebraic equations. The uniqueness of this research lies within the six-page instrument designed by the researchers to further elicit data on how Filipino high school students translate mathematical word problems into algebraic equations, and the reversal errors they commit. Hence, the qualitative discussions of the said errors will surely help Filipino Math teachers and education stakeholders in understanding the translation process carried out by their students.